Percutaneous nitinol‐based vascular closure device for large bore arterial access hemostasis: Results of a prospective multicenter study. Issue 2 (8th January 2020) - Barbash, Israel M.; Kornowski, Ran; Berkovitch, Anat; Assali, Abid; Erlebach, Magdalena; Guetta, Victor; Vaknin Assa, Hana; Lange, Ruediger; Segev, Amit; Ruge, Hendrik
Abstract: Background: Vascular complications during transcatheter aortic valve replacement (TAVR) still pose a significant concern regarding procedural safety. Designated closure devices for large‐bore vascular access are needed. Methods: Patients undergoing TAVR were prospectively enrolled into the study. The InSeal vascular closure device (VCD) achieves hemostasis by utilizing a crescent‐shaped nitinol scaffold covered by a biodegradable membrane, which is delivered at the arterial puncture site. The coprimary endpoints were predefined as hemostasis within 15 min following vessel access site closure and after activated clotting time falls below 200 s and the rate of related major vascular adverse events in first month. Results: A total of 50 patients were prospectively enrolled into the study, with an average age of 80.8 ± 7.4 years and 62% males. Hemostasis with the Inseal VCD was achieved in 94% of the patients with average time‐to‐hemostasis of 51 ± 97 s. The rates of in‐hospital vascular complications were 12% mostly driven by minor vascular complications (10%). Femoral artery stents were used in three patients due to failed hemostasis. Conclusions: Initial clinical experience indicates that a novel, nitinol‐based, large‐bore vascular closure device is safe and effective in achieving hemostasis after TAVR.